Regulated necrosis role in inflammation and repair in acute kidney injury - Juan Guerrero‐Mauvecin; Natalia Villar-Gómez; Sandra Rayego‐Mateos; Adrián M. Ramos; Marta Ruíz-Ortega; Alberto Ortíz; Ana B. Sanz (2023)
Acute kidney injury (AKI) frequently occurs in patients with chronic kidney disease (CKD) and in turn, may cause or accelerate CKD. Therapeutic options in AKI are limited and mostly relate to replacement of kidney function until the kidneys recover spontaneously. Furthermore, there is no treatment that prevents the AKI-to-CKD transition. Regulated necrosis has recently emerged as key player in kidney injury. Specifically, there is functional evidence for a role of necroptosis, ferroptosis or pyroptosis in AKI and the AKI-to-CKD progression. Regulated necrosis may be proinflammatory and immunogenic, triggering subsequent waves of regulated necrosis. In a paradigmatic murine nephrotoxic AKI model, a first wave of ferroptosis was followed by recruitment of inflammatory cytokines such as TWEAK that, in turn, triggered a secondary wave of necroptosis which led to persistent kidney injury and decreased kidney function. A correct understanding of the specific forms of regulated necrosis, their timing and intracellular molecular pathways may help design novel therapeutic strategies to prevent or treat AKI at different stages of the condition, thus improving patient survival and the AKI-to-CKD transition. We now review key regulated necrosis pathways and their role in AKI and the AKI-to-CKD transition both at the time of the initial insult and during the repair phase following AKI.